Dampak Subsidi Perikanan Dalam Perjanjian WTO Terhadap Nelayan di Indonesia - M. Miftahul Ilmi (Universitas Muhammadiyah Mataram, 2025)
Fisheries subsidies are a central issue in the context of international trade regulated by the WTO Agreement. For Indonesia, a country with a significant fisheries sector, these subsidies have a significant impact on the lives and livelihoods of fishermen. Although the WTO regulates various aspects of fisheries subsidies, their implementation and impact on Indonesian fishermen remain a major concern. This study explores the concrete impacts of fisheries subsidies within the framework of the WTO Agreement on the socio-economic conditions of fishermen in Indonesia. This analysis covers the implications of WTO policies on the welfare of fishermen, the protection of fishery resources, and the impact on trade and national food security. Considering this context, this study is not only relevant for understanding the dynamics of economic globalization in the fisheries sector, but also provides insights into policy strategies that can improve the welfare of Indonesian fishermen in the future.